Respuesta :
Answer:
13 years old
Explanation:
Let g and m represent grandfather's age now and my age now. The relation 5 years ago was ...
... g -5 = 5(m -5)
The relation in 3 years will be ...
... g +3 = 3(m +3)
Subtracting the first equation from the second, we get ...
... 8 = -2m +34
... 2m = 26 . . . . . add 2m-8
... m = 13
My age now is 13.
Answer:
13 years
Step-by-step explanation:
5 years ago, let the grandchild's age to be x so the grandfather's age will be 5x.
3 years from now, the grandchild's age will be x+8 (x+3+5) and the grandfather's age will be 5x+8 (5x+3+8).
So we can establish an equation:
[tex]5x+8=3(x+8)[/tex]
[tex]5x+8=3x+24[/tex]
[tex]5x-3x=24-8[/tex]
[tex]2x=16[/tex]
[tex]x=8[/tex]
Therefore, the present age of the grandchild is x+5 = 8+5 = 13 years and the present age of the grandfather is 5x+5 = 5(8)+5 = 45.